Continuous use of fitness apps and shaping factors among college students: a mixed-method investigation - Zhang, Xiaoxiao; Xu, Xiaoge (Chinese Nursing Association, 2020)
Objective: This current study pursued an exploration of the psychological mechanism that determines college students’ continuance intention to use fitness apps. Methods: This current study adopted a mixed methods research that composed two distinct phases. Study 1 was quantitative research that helped to identify determinants of Chinese college students’ continuance intention to use. A self-reported questionnaire was completed by 379 college students to ascertain their user experience. Study 2 was qualitative research. A semi-structured interview was conducted with a sample of 10 college students. Study 2 can be seen as a follow-up study and it pursued an in-depth understanding on how college students use fitness apps in the everyday life and their views towards study 1’s major findings. Results: The results revealed that five factors (confirmed usefulness, confirmed ease of use, satisfaction, fitness achievement and social connection) were found to significantly and positively affect college students’ continuous intention to use fitness apps. Entertainment did not show obvious impact. In the interview, college students reported that even if they don't obtain entertainment from fitness apps, they will still push themselves to use them, because they have a very specific goal when using fitness apps, which is to achieve health and fitness. Conclusion: These findings indicated that successful fitness apps should make users feel convenient to use and indeed improves the fitness user's efficiency. Besides, people are more eager to get the information with strong credibility with the negligible effort. This implies more efforts should be made to design apps that can provide high-quality services. Moreover, if apps designers can pay more attention to protecting the personal information and data, it will inspire more people to use social connection functions.